Determinação do potencial de seqüestro de carbono na recuperação de matas ciliares na região de São Carlos - SP - Martins, Osvaldo Stella (Universidade Federal de São Carlos, 2004)
The loss of natural forest coverage reached 86% from total forested areas in São Paulo State until the year 2003. This scenario gets more critical when gallery forests are taken into acount. This particular kind of forests offers ecological services even more important than normal forests. Even inside law protected areas as well as permanently protected areas (CPA) riverside forests have been progressively devastated. Clearing of riverside forests, besides other problems, causes water resources depletion as the rivers lose this kind of natural protection. A critical factor on riverside forest recovery is related to the high costs on planting and maintaining reforested areas. This work presents an analysis developed to evaluate the potential carbon sequestration on recovering gallery forests, aiming to obtain CERs (Certified Emission Reductions) from a CDM (Clean Development Mechanism) project, as foreseen in the Kyoto Protocol. The proposal is divided in four main steps. In the first step the target area is defined and the total CPA area is marked. Then, which part of the CPA area is still forested and which part is not are determined. During the third step the local gallery forest main characteristics are analised. In the fourth step the information regarding development duration, population size of each tree species and individual diameter at breast heigth (DBH) are used to calculate the amount of carbon accumulated in the reforested area. Finally the proposal is applied for the micro-basin of Jacaré-Guaçu River, in São Carlos (21°30´S, 47°30´W) region, São Paulo State, Brazil. The results show an accumulation of 95tC/ha considering above ground and roots biomass and a cost for sequestred carbon of US$ 7/tCO2eq. Considering the actual CER´s market value, US$ 5/tCO2eq the carbon credits are not enough to meet the costs of reflorestation but represents a valuable contribution.
Keywords: Ecologia; Mudanças climáticas; Efeito estufo; Mata ciliar; Sequëstro de carbono; CIENCIAS BIOLOGICAS::ECOLOGIA